A study on assessment of Agnibala and Koshtha in Amavata and their association with inflammatory markers in R.A. - Yadav, Anamika; Dubey, Sushil Kumar; Anand, Vivek (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: Mandagni has been considered one of the primary indigenous factors for the manifestation of Amavata, so there might be the effect of the causative factors affecting the status of Agnibala of an individual. Hence an attempt can be made to observe the status of Agnibala and Koshta with particular reference to different inflammatory markers present in subjects of Aamvata. Material and Method: The main goal of the study was to evaluate the Agnibala and Koshtha of the Amavata Patients and to determine the relationship between Agni and Koshtha with the inflammatory parameters of Rheumatoid Arthritis as the characteristics of Amavata are similar to Rheumatoid Arthritis. The aims and Objectives of the study include the Assessment of Koshtha using a self-developed Standard Proforma for Koshtha Assessment (KAQ). Agnibala, using a standard proforma developed by Singh A et al., 2016. Amavata patients were encouraged to undertake Haematological examinations along with Investigations of Inflammatory markers of Rheumatoid arthritis and their reports were collected and analysed for additional statistical analysis. BHU’s CCI lab and other standard laboratories were used for the research. The data were then statistically analysed. Results and Conclusion: According to the Agni Bala assessment from this study, it can be said that Mandagni is the main causative factor for the development of Amavata. A good correlation has been found between symptoms of Amavata and ACR criteria of Rheumatoid Arthritis from this study. A significant association was found between Madhyam Koshtha and Amavata as provocative factors. There is also a significant correlation found between Koshtha and Agni.